The role of English Tutors at San Juan Bautista Private University for Absolute Beginner English Students: A case study. - Gordillo Rios, Ana Rosa (2018)
The main purpose of this work is to support San Juan Bau tista Private University s students who did not have the opportw1ity to study English properly at their chools glving them tbe necessary personalized pedagogical teaching, so that they can understand how they should study the Language and in this way they would be able to join tbeir future Engüsh studying groups without problems. Tlle second objective is to prevent tbese student to develop learned belplessness or to help them overcome thi problem witb tbe personal teaching of an Englisb academic tutor. Historie evidence, afier more !han 40 years of experience, shows tbat a language cannot be lcarot within the range of such a limited time of exposure. For this reason my proposal is that students who have very little or no English knowledge, should count on English tutoring to guide them in the beginning of their learning process.